Literary Language and Classification of Functional Styles in French - Akhmedova Gulnoza Hayot Qizi (Zien Journals, 2022)
Literary language is the main, supra-dialect form of language existence, characterized by more or less processing, poly-functionality, stylistic differentiation and a tendency to regulation. By its cultural and social status, the literary language opposes territorial dialects, different types of everyday colloquial koine and vernacular - as the highest form of language existence [LES, 2008, Electronic resource].
Keywords: Functional Styles; French Language; Language Classification